Pre-operative management of fracture blisters: a systematic review - Ishtar Redman; Kapil Sugand; Aashtad Daruwalla; Andrew Clark (EFORT Open Reviews)
Purpose: The pre-operative management of fracture blisters is an area of uncertainty within trauma and orthopaedic surgeries. Management strategies vary significantly between and within orthopaedic departments across the United Kingdom. The purpose of this systematic review was to comprehensively appraise and synthesize the existing literature pertaining to this topic, highlighting current practices and areas for ongoing research. Methods: Extensive electronic literature searches were performed on PubMed/MEDLINE (January 1946–May 2024), Embase (January 1974–May 2024) and Cochrane library (January 1933–May 2024) databases. The search terms were as follows: (fracture blister OR bone blister*) AND (dress* OR drain* OR aspirat* OR deroof* OR manage*). These keywords were searched in the subject headings, in title and in abstract. Results: The results of the search methodology revealed five articles, which represented the best evidence to the clinical question. These papers reported on rates of wound healing and post-operative infection, time to surgical readiness and treatment costs, following varying treatment modalities in 1162 patients. The authors, publication dates, countries, patient groups, study outcomes and results of these papers are tabulated in Supplementary Table 1. Conclusion: Fracture blisters pose a significant challenge in clinical practice, leading to delays in surgery, suboptimal surgical approaches and complications in wound healing post-operatively. Currently, there is no consensus describing the optimal management of these blisters. This review challenges the conventional belief that fracture blisters are sterile, highlighting that the application of topical agents to the deroofed blister bed may expedite surgical readiness.